(untitled) (Research, Society and Development, 2023)
This review aimed to analyze how the COVID-19 pandemic had repercussions on the daily life of cancer patients. It is a narrative literature review, in which 39 articles were selected for composition, being found in the BVS, PubMed and SciELO databases and in the official websites INCA, WHO, SBIM, CNS, FIOCRUZ and MS. The results of the study showed the high risk of the virus for the cancer patients, the low attendance at treatment centers and the mental consequences of this pandemic context. In addition, the use of telemedicine, immunization and the importance of psychological support as strategies for patients to cope with the pandemic were verified. Furthermor, the mental impact on professionals working in oncology was highlighted, showing the need to expand this emotional support.